2014
DOI: 10.1007/s00399-014-0310-1
|View full text |Cite
|
Sign up to set email alerts
|

Duale AV-nodale Nicht-Reentry-Tachykardie

Abstract: The DAVNNT seems to be more common than previously thought. This important differential diagnosis needs to be taken into consideration as slow pathway modulation can be curative while a misdiagnosis, such as atrial fibrillation or ventricular tachycardia might result in over-treatment in patients with this arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Hence, it is likely that DAVNNT is underdiagnosed. In a review of 68 cases of DAVNNT, 48 of them were initially misdiagnosed, 1 with 4 being mislabeled as ventricular tachycardia, similar to our case 5, 6, 7. Delay in diagnosis can lead to ineffective treatment with antiarrhythmic medications and/or development of a tachycardia-induced cardiomyopathy.…”
Section: Discussionsupporting
confidence: 58%
“…Hence, it is likely that DAVNNT is underdiagnosed. In a review of 68 cases of DAVNNT, 48 of them were initially misdiagnosed, 1 with 4 being mislabeled as ventricular tachycardia, similar to our case 5, 6, 7. Delay in diagnosis can lead to ineffective treatment with antiarrhythmic medications and/or development of a tachycardia-induced cardiomyopathy.…”
Section: Discussionsupporting
confidence: 58%
“…Almost all patients with DAVNNT have been treated with slow pathway modulation or ablation [ 6 , 8 ]. These case reports and two small single-centre experiences including three [ 14 ] and five patients [ 10 ], respectively, indicate high procedural success rates. Most of these patients were treated with radiofrequency ablation, only two patients underwent cryo-ablation [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 81%
“…This diagnostic tool has been proposed as gold standard [ 8 ], but the correct diagnosis may be complicated by its heterogeneous appearance leading to several differential diagnosis consisting of atrial fibrillation (AF), sporadic junctional extrasystoles, parasystoles, ventricular tachycardia or AVNRT with retrograde 1:2 conduction block [ 8 , 9 ]. The rarity and possible mimicking of other, more common arrhythmias has led to initial misdiagnoses in about 70% of all published cases [ 8 ] and to an underestimation of this ‘chameleon of the AV node’ [ 8 10 , 14 ]. Furthermore, patients treated for misdiagnosed AF by oral anticoagulation or non-indicated implantations of implantable cardioverter defibrillators (ICDs)—even with the appearance of inadequate shocks—emphasize the relevance of a better understanding and implementation of this phenomenon in daily clinical routine [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 The presence of VA dissociation and rate criteria for ventricular activation greater than atrial activation may be misinterpreted as VT, especially when wide QRS complex with variable morphologies are present. 3 , 4 , 5 Previous reports showed that patients with DAVNNT and wide QRS tachycardia were misdiagnosed as VT and received inappropriate intracardiac defibrillator device therapy. The misdiagnoses were based upon interpretation of atrial and ventricular device electrograms that satisfied both rate and V>A criteria for ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…The misdiagnoses were based upon interpretation of atrial and ventricular device electrograms that satisfied both rate and V>A criteria for ventricular tachycardia. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%